Efektivitas Pesan Protokol Kesehatan Penanggulangan COVID-19 dari Sudut Pandang Masyarakat Kota Mataram - Allen Tiffanie Mosse; I Wayan Suadnya; Baiq Vira Safitri (Program Studi Ilmu Komunikasi Universitas Mataram, 2021)
The people of West Nusa Tenggara especially in Mataram City, also felt the impact of COVID-19 pandemic. Although the COVID-19 information and its health protocols has been spread widely, Mataram’s residents dealing with the pandemic in different behaviors. This becomes a question of the effectiveness of COVID-19 health protocol message conveyed to Mataram’s residents by the government and medical team as the parties who makes policies and tackles this pandemic. This research aims to determine the form, process of communication messages, and the effectiveness of COVID-19 health protocol message from the perspective of Mataram local residents. This research uses qualitative descriptive method, with data collection techniques through observation, interviews, and documentation. The data analysis technique uses Miles and Huberman model analysis, and the data checking technique uses triangulation method. The results indicate that the government and medical team in conveying the COVID-19 health protocol message used interpersonal communication forms, primary and secondary communication message processes, and the health protocol messages conveyed were effective. However, there are still obstacles that hinder the process of understanding and implementing the COVID-19 health protocol. In this research also provides recommendations to help improve the pattern of conveying COVID-19 health protocol messages to public.